The influence of delayed treatment due to COVID-19 on patients with neovascular age-related macular degeneration and polypoidal choroidal vasculopathy. (June 2021) - Zhao, Xinyu; Meng, Lihui; Luo, Mingyue; Yu, Weihong; Min, Hanyi; Dai, Rongping; Koh, Adrian; Chen, Youxin
Purpose: To explore the impact of coronavirus disease 2019 (COVID-19) on the prognosis of patients with neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV), and share the experience in managing them during pandemics. Method: This is a retrospective study of nAMD and PCV patients treated at Peking Union Medical College Hospital from 31 December 2019 to 1 August 2020. Baseline demographic and clinical characteristics, best corrected visual acuity (BCVA), optical coherence tomography (OCT) features, duration of delayed treatment and number of anti-vascular endothelial growth factor (VEGF) injections were analyzed. Results: A total of 130 nAMD patients (155 eyes) and 76 PCV patients (89 eyes) were identified. Compared to the conditions before COVID-19, the BCVA of delayed cases decreased significantly, and the proportion of patients presenting with sub-macular scar was significantly greater in the delayed treatment group ( p  < 0.05). The BCVA of non-delayed cases remained stable, with the percentage of patients with disease activity sub-retinal fluid and hemorrhage at the fovea decreasing significantly ( p  < 0.05). The stable cases who did not require anti-VEGF treatment had significantly worse baseline and final BCVA, these patients were likely to be chronic and 'burnt out' cases with significantly worse anatomical structures ( p  < 0.05). Conclusions: The delayed cases due to the pandemic suffered compromised visual function and a higher rate of sub-macular scar formation, while the visual function of non-delayed cases remained stable with favorable anatomical outcomes, suggesting the importance of regular follow-up for nAMD and PCV patients. Besides, effective measures of hospitals during pandemics are crucial to provide timely treatment for chronic disease.